Construction and empirical analysis of the ideological and political teaching ability inspection model of professional teachers in universities empowered by digital intelligence - Yang, Xueying; Ye, Wenxin; Wei, Jia; Yu, Huanyang (Frontiers in Psychology, 2025)
The development of digitalization, big data, and information technology has profoundly affected higher education. College and university teachers operate within a new innovative ecology, encompassing everything from the acquisition of information resources to the presentation of teaching methods across space, time, patterns, content, and pedagogy. Under the concept of comprehensive digital education, the efficient integration of curriculum expertise and professional education, supported by digital technology can enhance the digital ability and proficiency of professional course instructors in higher education and improve the goal of human education. To this end, the digital intelligence-empowered inspection model for college professional teachers’ ideological and political teaching ability inspection is constructed to enable them to diagnose and assess their own ideological and political teaching capacity and to plan the direction of their development and enhancement. Colleges, universities, and management organizations can intuitively understand the performance levels and training needs related to professional teachers’ ideological and political teaching ability, allowing them to improve this ability in a targeted and practical way.